Analisis Gaya Bahasa Dalam Iklan Komersial Minuman Berkarbonasi - Filud Jeannity Lignuma; Sasabila Alfi Rahmatin; Lailatul Mufarihah; Zanul Muttaqin; Eni Nurhayati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Advertisements for soft drinks are less clear because they use economy of words. Noting that the arrangement and choice of diction, as well as the accuracy of punctuation, are advertising styles or features that must be paid attention to if the advertisement is to be closer to the audience. Theories such as word economy and language variety are the focus of the author's research. Advertisements for fizzy drinks such as Coca-Cola, Sprite, and Fanta are used. The first advertisement has a persuasive, informative and reminiscent impression. However, the language style used in the advertisement depends on the purpose of the advertisement and the person being spoken to. Different uses, formalities, and means of language. In advertising, icons, symbols, models and texts are identified through language analysis. The aim or intent of advertising is expressed by verbal media, such as language, and non-verbal media, such as images, colors and models. Images and models, which are visual representations of product offerings, consist of model expressions, symbols, or icons used as markers to attract customer attention.